ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI PRAKTIK BIDAN MANDIRI - Auliya Fitriana Noorzaman; Ady Tia Ramadhan (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to understand how patients interpret their service experiences at the Independent Midwife Practice of Hj. Iim Maryati, located in Batujajar, West Bandung. The main focus of this research is to explore patients' perceptions of service quality based on the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy, as well as how these experiences influence their level of satisfaction or dissatisfaction. This research employs a qualitative approach using a case study method. Data were collected throughin-depth interviews, direct observation, and documentation. The data were then analyzed using Miles and Huberman's interactive model, which includes data reduction, data display, and conclusion drawing. The results showed that each dimension of service quality was subjectively interpreted by patients based on their personal experiences. Factors such as interpersonal communication, emotional comfort, and empathy of health workers played a major role in shaping patient satisfaction. This study recommends a more humanistic and patient-centered service approach to improve the quality of independent midwifery practice services. Keywords: patient experience, service quality, satisfaction, independent midwife, case study, SERVQUAL.